Application of Integrated Methods to Improve the Technological Properties of Steel; Key Engineering Materials; Vol. 736 : Materials and their Application - Fedoseev S. N. Sergey Nikolaevich; Valuev D. V. Denis Viktorovich; Mamadaliev R. A.; Sokolov P. N. (2017, 2017)
Title screen